A comprehensive review on catalytic O-alkylation of phenol and hydroquinone. Issue 2 (3rd April 2023) - Bhongale, Priyanka; Joshi, Sunil; Mali, Nilesh
ABSTRACT: The alkylation process involves two competitive paths of O- and C- alkylation and achieving better selectivity for desired products is a very challenging problem. The development of new process for synthesis of O- methylated products of phenol and dihydric phenols is a subject of high industrial and academic interest. Alkyl phenyl ethers, especially anisole and 4-methoxyphenol, have captivated significant interest due to their increasing applications in pharmaceutical industries. The main emphasis of the present review is to explore the recent development in two catalytic O- alkylation processes. The first process is O- methylation of phenol into anisole and another is selective mono O- methylation of hydroquinone into 4-methoxyphenol. The present article covers O- alkylation methods with methanol and dimethyl carbonate as alkylating agent over various acidic and basic catalytic systems. The catalyst systems analyzed involves Bronsted and Lewis acidic and basic ionic liquids, conventional acids, metal oxides, solid acid and basic catalysts, hydrotalcites, various zeolites and heteropolyacids. The mechanistic behavior of alkylation reactions in presence of different catalytic system is reviewed critically which is important to design new and/or modified catalyst in order to maximize the yield of desired product. Additionally, an influence of reaction parameters, role of catalyst and their active sites on product distribution is described. The review paper gives useful insight for researchers in the field of catalysis and reaction engineering of alkylation reactions. Understandings of the reaction pathways will help in developing reliable kinetic models necessary for process scale-up to industrial scale reactor system.